THE BENER MERIAH DISTRICT HEALTH OFFICE’S STRATEGY FOR PREVENTING CHRONIC ENERGY DEFICIENCY IN PREGNANT WOMEN - Sazarwan Mukhra; Delfi Suganda (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2026)
This study aims to analyze the strategies of the Health Office of Bener Meriah Regency in preventing CED among pregnant women as an effort to reduce stunting prevalence, with the main challenges being limited regional budget capacity and low participation of pregnant women and the community. This study employs David’s (2014) strategic management theory, which consists of strategy formulation, implementation, and evaluation stages. The research uses a qualitative method with a case study approach. The results indicate that CED prevention strategies remain predominantly top-down and are largely aligned with central government policies due to limited local fiscal capacity. The implemented strategies focus on the provision of supplementary feeding programs, nutrition education, and monitoring of pregnant women’s nutritional status. Strategy implementation involves village midwives, nutritionists, and health cadres, supported by a tiered evaluation system through daily, weekly, and monthly reporting. These strategies have contributed to a reduction in stunting prevalence from 19.95% in 2021 to 8.96% in 2024, although challenges related to funding constraints and community participation persist. This study recommends the development of more contextualized CED prevention strategies, optimization of the utilization of Health Operational Assistance (BOK) funds, and adjustment of program implementation to local socioeconomic conditions.